IMPROVING DIGITAL BANKING THROUGH RISK ASSURANCE: TAM MODIFICATION ANALYSIS - Marlina Wijayanti, Dwi; Al-Banna, Hasan; Nurdany, Achmad (Bank Indonesia, 2024)
The rapid growth of digital banks has been followed by changing customer behaviour patterns. On the other hand, customer perceptions of digital banks are that they still carry considerable risk. Therefore, the role of institutions in providing certainty and security guarantees for digital banking customers is very important. Based on this situation, this research explores what factors can encourage individuals to use digital banks, which are currently growing quite rapidly through the role of institutions. The Technological Acceptance Model (TAM) is used as a construct in exploring individual behaviour in reaction to technological innovation in digital banks. In addition, risk guarantees from government institutions are also explored as safeguarding customer security. The sample for this study were 977 digital bank users. Data was collected through a self-administered survey. The results show that perceived service quality (PSQ), service innovation (SI), perceived usefulness (PU), perceived ease of use (PEoU), attitude, and behavioural intentions are factors that encourage actual use of digital banking services. It is also known that perceived risk assurance moderates the relationship between attitude and behavioural intention. This research contributes to policy makers for the expansion of digital bank market share through appropriate marketing strategies for digital banks, as well as strategies to increase deposit insurance literacy.